Acid digestion of carbonates using break seal method for clumped isotope analysis. (19th December 2018) - Fosu, Benjamin R.; Ghosh, Prosenjit; Mishra, Divya; Banerjee, Yogaraj; K, Prasanna; Sarkar, Amrita
Abstract : Rationale: Acid digestion of carbonates to release CO2 is a crucial and sensitive step in sample preparation for clumped isotope analysis. In addition to data reduction and instrumental artefacts, many other uncertainties in the clumped isotope analysis of carbonates arise from the method used for the preparation of CO2 . We describe here an in‐house‐designed reaction vessel that circumvents degassing and contamination problems commonly associated with the McCrea‐type digestion protocols. Methods: We designed a leak‐free break seal reaction vessel (made of Pyrex™) suitable for prolonged acid digestion at 25°C. Using this new vessel, several carbonate reference materials widely used in the clumped isotope community and other in‐house laboratory standards were acid‐digested and analysed for their δ 13 C, δ 18 O and Δ47 values with a dual inlet MAT 253 isotope ratio mass spectrometer following standard gas chromatography purification and data evaluation protocols. Results: Long‐term reproducibility in Δ47 determination was established using international references and in‐house working standards as follows (mean and SE): Carrara‐1 (0.395 ± 0.002‰, n = 43), Carrara‐2 (0.441 ± 0.003‰, n = 22), OMC (0.587 ± 0.004‰, n = 16), NBS 19 (0.393 ± 0.005‰, n = 10), NBS 18 (0.473 ± 0.003‰, n = 5), ETH 1 (0.271 ± 0.005‰, n = 7), ETH 3 (0.698 ± 0.005‰, n = 3), MZ (0.715 ± 0.002‰, n = 3) and several others. Conclusions: A new method using a break seal tube was found to be efficient for the clumped isotope analysis of carbonates that require longer reaction time at 25°C. This method yields good precision in Δ47 analysis and was found to be suitable for acid digestions at any desired temperature.